Elder abuse prevalence in community settings: a systematic review and meta-analysis. Issue 2 (February 2017) - Yon, Yongjie; Mikton, Christopher R; Gassoumis, Zachary D; Wilber, Kathleen H
Summary: Background: Elder abuse is recognised worldwide as a serious problem, yet quantitative syntheses of prevalence studies are rare. We aimed to quantify and understand prevalence variation at the global and regional levels. Methods: For this systematic review and meta-analysis, we searched 14 databases, including PubMed, PsycINFO, CINAHL, EMBASE, and MEDLINE, using a comprehensive search strategy to identify elder abuse prevalence studies in the community published from inception to June 26, 2015. Studies reporting estimates of past-year abuse prevalence in adults aged 60 years or older were included in the analyses. Subgroup analysis and meta-regression were used to explore heterogeneity, with study quality assessed with the risk of bias tool. The study protocol has been registered with PROSPERO, number CRD42015029197. Findings: Of the 38 544 studies initially identified, 52 were eligible for inclusion. These studies were geographically diverse (28 countries). The pooled prevalence rate for overall elder abuse was 15·7% (95% CI 12·8–19·3). The pooled prevalence estimate was 11·6% (8·1–16·3) for psychological abuse, 6·8% (5·0–9·2) for financial abuse, 4·2% (2·1–8·1) for neglect, 2·6% (1·6–4·4) for physical abuse, and 0·9% (0·6–1·4) for sexual abuse. Meta-analysis of studies that included overall abuse revealed heterogeneity. Significant associations were found between overall prevalence estimates and sample size, income classification, and method of data collection, but not with gender. Interpretation: Although robust prevalence studies are sparse in low-income and middle-income countries, elder abuse seems to affect one in six older adults worldwide, which is roughly 141 million people. Nonetheless, elder abuse is a neglected global public health priority, especially compared with other types of violence. Funding: Social Sciences and Humanities Research Council of Canada and the WHO Department of Ageing and Life Course.